Tourist Guide Behavior of Margorejo Tourism Community Towards Timor Deer Reproduction - Samsudewa, Daud; Pajriah, Leli; Casmuti, Casmuti; Prayoga, Kadhung (Universitas Halu Oleo, 2022)
The aim of this research is to know the alteration of behavior of tourist guide after accompaniment towards Timor deer reproduction. This research was done on October 2018 to November 2019 in Margorejo village, Dawe District, Kudus Regency. Experimental method with one group pre-test post-test design were used in this research. Fifteen tourist guide as responden in this research. Interview and observation were used for data retrieval. Knowledge, attitude and skills were used as variable. Descriptive analysis were used. The results of this research showed that knowledge of tourist guide was increased 50.5%, from 26.66% to 77.16%. The attitude of the tourist guide was increased 39.17%, from 29.33% to 68.50%. The skills of tourist guide was increased 40.84%, from 26.16% to 67.00%. The conclusion of this research is the aaccompaniment was success to improve the knowledge, attitude and skills of tour guide in Margorejo village toward reproduction of Timor deer.Keywords: behavior, timor deer reproduction, tourist guide